2021
DOI: 10.51388/20.500.12265/138
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thinking for an Inclusive World: A Resource for Educators to Learn and Lead

Abstract: Technology is becoming more integral across professional fields and within our daily lives, especially since the onset of the pandemic. As such, opportunities to learn computational thinking are important to all students—not only the ones who will eventually study computer science or enter the information technology industry. However, large inequalities continue to exist in access to equipment and learning opportunities needed to build computational thinking skills for students that experience marginalization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…In terms of the learning context, researchers indicated that programming and CT are everywhere in children’s lives; integrating programming and CT into their daily routines and tasks, such as brushing teeth, washing hands, or making objects with clay, offers meaningful learning contexts ( Lee and Junoh, 2019 ; Mills et al, 2021 ). However, according to interviews, Ms. Wu solely taught programming and CT through whole-group activities and was unaware of the learning opportunities present in daily activities and other learning domains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the learning context, researchers indicated that programming and CT are everywhere in children’s lives; integrating programming and CT into their daily routines and tasks, such as brushing teeth, washing hands, or making objects with clay, offers meaningful learning contexts ( Lee and Junoh, 2019 ; Mills et al, 2021 ). However, according to interviews, Ms. Wu solely taught programming and CT through whole-group activities and was unaware of the learning opportunities present in daily activities and other learning domains.…”
Section: Discussionmentioning
confidence: 99%
“…CT involves the ability to break down complex problems into smaller parts, identify similarities among and within problems, develop step-by-step solutions and so on ( Yang et al, 2022 ; Zeng et al, 2023 ). Programming, on the other hand, is the process of writing codes to implement a particular task or solve a particular problem ( Mills et al, 2021 ). CT and programming are closely intertwined, with each relying on and enhancing the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are all naturally inclined to employ inductive thinking and deductive thinking in everyday life. They are the two major cognitive competencies at the root of the CT skillset ( Wing, 2006 ; Yaşar et al, 2016 ; Yaşar, 2018 ; Denning and Tedre, 2019 ; Mills et al, 2021 ), which are often cited as abstraction and decomposition skills. We all employ computational thinking by the virtue of having a computational mind.…”
Section: Introductionmentioning
confidence: 99%
“…Computational thinking is the pedagogical basis of our workshop. Computational thinking refers to the cognitive processes involved in using computers to solve problems, including but not limited to problem reformulation, recursion/algorithmic thinking, problem decomposition, abstraction, pattern recognition, data visualization and analysis, selection of tools, systematic testing/debugging, automation, and computational modeling [26][27][28][29]. These cognitive processes are useful for learning programming, and they can also be used for improving problem solving more generally with or without a computer.…”
Section: Introductionmentioning
confidence: 99%